Flash Builder and Flash Catalyst The New Workflow - Peeters, Steven (Apress : Imprint: Apress, 2010)
The Flash Platform is changing. Flash Builder and Flash Catalyst have brought a new separation of design and coding to web development that enables a much more efficient and streamlined workflow. For designers and developers used to the close confines of Flash, this is a hugely liberating, but at first alien concept. This book teaches the new workflow for the Flash platform. It gives an overview of the technologies involved and provides you with real-world project examples and best-practice guidelines to get from design to implementation with the tools at hand. Includes many examples Focuses on real-world situations Covers designer and developer workflow.